Equações de Predição das Exigências de Proteína Bruta para Matrizes Pesadas em Crescimento - Filardi, R. D. (2000)
The objective of this work was to determine the crude protein requirements for broiler breeder pullets, using the factorial method. The protein requirements for maintenance were obtained by comparative slaughter technique and also by nitrogen balance technique, as usual. In the case of comparative slaughter technique we have examined the nitrogen retained as function of different nitrogen intake levels (ad libitum, 54, 24 and 19% of the ad libitum). For the nitrogen balance technique it has been investigated the nitrogen balance as function of nitrogen intake, at different protein levels (16, 10 6 and 3% CP). The results obtained were 3.77 and 2.02 CP/kg(0.75)/day for comparative slaughter and nitrogen balance techniques, respectively. The protein requirements for weight gain were achieved by weekly following the nitrogen level in the body, during the period from 3 to 20 weeks of age. The results were 350, 406 and 463 mg of CP/g of gain in the phases of 3 to 8, 9 to 14 and 15 to 20 weeks, respectively.